RESTORATION AND DEVELOPMENT OF AUDITORY SPEECH RECEPTION THROUGH A COCHLEAR IMPLANT (Conference Zone, 2022)
Advances in medicine and special pedagogy in recent years have had a positive impact on the level of adaptation and rehabilitation of children with hearing impairments, as well as their social adaptation through early correction of hearing and speech problems.